2018
DOI: 10.1021/acsanm.8b01765
|View full text |Cite
|
Sign up to set email alerts
|

Ni/Al Layered Double Hydroxide and Carbon Nanomaterial Composites for Glucose Sensing

Abstract: Layered double hydroxides (LDHs) have been combined with graphene and/or carbon nanotubes to prepare new composite materials with fascinating electrochemical features. For the first time, this work describes the development of an electrosynthesis protocol that allows the deposition of thin films of a Ni/Al LDH on glassy carbon electrodes previously modified with carbon nanomaterials. Three different approaches (potentiostatic, galvanostatic and potentiodynamic) were investigated in order to identify the best p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…28 Redox property of the LDH can be promoted using transition metals (such as Co, Ni, Mn, and Fe), which undergo a Faradaic reaction via an electrochemical pathway in an appropriate potential range. 29 The LDH materials can conduct electricity due to electron hopping between metal centers that are close together or due to displacement of ion outside or inside the material. Therefore, the LDH have been considered as pseudo capacitive materials to produce supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…28 Redox property of the LDH can be promoted using transition metals (such as Co, Ni, Mn, and Fe), which undergo a Faradaic reaction via an electrochemical pathway in an appropriate potential range. 29 The LDH materials can conduct electricity due to electron hopping between metal centers that are close together or due to displacement of ion outside or inside the material. Therefore, the LDH have been considered as pseudo capacitive materials to produce supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ratio of the two metals in the electrodeposited compound is not strictly the same as present in the electrolytic solution because of the concentration gradients originating during the synthesis, especially when a long potential pulse is applied. Our group [ 33 , 34 , 35 ] has demonstrated that the potentiodynamic approach, which is based on the application of few CV cycles in the cathodic potential range, provides a reproducibility of the deposit which is much better than the one achieved with either the galvanostatic or potentiostatic methods. This is due to the strong reduction of cations concentration gradients in the diffusion layer, which are typical of the potentiostatic approach, thus allowing the restoration of the initial concentrations at the electrode surface.…”
Section: Preparation Of the Devicesmentioning
confidence: 99%
“…Therefore, the same strategies can be employed to enhance the sensors’ performance. Composite materials based on LDHs and carbon nanomaterials have been synthesized to fabricate sensors for enzyme-less detection of glucose [ 34 , 118 , 119 ], guanine [ 120 ], H 2 S [ 121 ], and dopamine [ 122 ] displaying superior performance thanks to the enhanced electrical conductivity. The sensor performances can be improved increasing the accessibility to the redox-active sites, if the conductive support is chemically modified with ultrathin LDH layers [ 123 , 124 , 125 ].…”
Section: Applicationsmentioning
confidence: 99%
“…A smart example presented by Gualandi et al [79] consisted of the development of a new composite material with electrochemical features combining LDHs with graphene and/or carbon nanotubes. Many LDHs' applications are restricted because of their low electrical conductivity decay during device operation due to the volume change associated with a variation of the redox state of the material.…”
Section: Glucose Determinationmentioning
confidence: 99%